Modulação de ciclos de luz como uma estratégia para redução de custos energéticos em fotobiorreatores - Maroneze, Mariana Manzoni (2016)
Microalgae are photosynthetic microorganisms, which in turn, have versatility to associate CO2 sequestration processes with parallel production of inputs. However, one of the operational problems of this technology refers to availability of light energy in whole periods of time. For this, it is known that photosynthetic metabolism allows accumulation of energy during the supply of light, thus ensuring that the process can be continued for some time in the absence of light. In this sense, the aims of this work were: (i) evaluate the effect of long term light cycles in the cultivation of photosynthetic microalgae Scenedesmus obliquus (CPCC05), (ii) evaluate the effect of frequency photoperiod on Scenedesmus obliquus (CPCC05), (ii) evaluate the effect of short light cycles in photosynthetic microalgae cultivation of Scenedesmus obliquus (CPCC05), (iv) evaluate the lipids synthesis, (V) determine the qualitative profile of the lipid fraction, (vi) evaluate the electrical energy demand of different cycles of light. The results demonstrated that the microalgae Scenedesmus obliquus (CPCC05) was able to store enough energy to keep your metabolism for up to 2 hours of continuous darkness. Among all photoperiods, the 22:2 h fractionated at 24 and 48 cycles per day presented the highest lipid productivity (2:56 mg/L.h). Considering the electric energy demand, the photoperiods 0.50: 00:50 s (light: dark) and 22:2 h at 24 frequencies per day showed the best cost benefit for the production of microalgal biomass. The results showed that the modulation of the light cycles is a viable alternative to significantly reduce energy costs in photobioreactors.